Dyskinetic cerebral palsy in Europe: trends in prevalence and severity. Issue 12 (12th May 2009) - Himmelmann, K; McManus, V; Hagberg, G; Uvebrant, P; Krägeloh-Mann, I; Cans, C
Abstract : Objective: To describe the trends for and severity of dyskinetic cerebral palsy in a European collaborative study between cerebral palsy registers, the Surveillance of Cerebral Palsy in Europe (SCPE). Methods: The prevalence of dyskinetic cerebral palsy was calculated in children born in 1976–1996. Walking ability, accompanying impairments and perinatal adverse events were analysed. Results: 578 children had dyskinetic cerebral palsy, of whom 70% were born at term. The prevalence per 1000 live births increased from 0.08 in the 1970s to 0.14 in the 1990s. For the 386 children (70%) with a birth weight of ⩾2500 g, the increase was significant (0.05 to 0.12). There was a concurrent decrease in neonatal mortality among children with a birth weight of ⩾2500 g. Overall, 16% of the children walked without aids, 24% with aids and 59% needed a wheelchair. Severe learning disability was present in 52%, epilepsy in 51% and severe visual and hearing impairment in 19% and 6%, respectively. Accompanying impairments increased with motor severity. In children born in 1991–1996, perinatal adverse events, that is an Apgar score of <5 at 5 min and convulsions before 72 h, had occurred more frequently compared with children with bilateral spastic cerebral palsy (BSCP, n = 4746). Children with dyskinetic cerebral palsy had more severe cognitive and motor impairments than children with BSCP. Conclusions: The prevalence of dyskinetic cerebral palsy appears to have increased in children with a normal birth weight. They have frequently experienced perinatal adverse events. Most children have a severe motor impairment and several accompanying impairments.